Crystal structure of bis{hydridotris(3-trifluoromethyl-5-methylpyrazolyl-1-yl)borato-κN 3}manganese(II), C30H26B2F18MnN12 - Ikarugi, R.; Fujisawa, Kiyoshi; Tiekink, Edward R. T. * (De Gruyter Open, 2022)
C30H26B2F18MnN12, triclinic, P1 (no. 2), a = 10.5322(3) Å, b = 10.6475(4) Å, c = 10.9890(4) Å, α = 111.755(3)°, β = 99.100(2)°, γ = 112.740(3)°, V = 988.07(7) Å3, Z = 1, Rgt(F) = 0.0338, wRref(F2) = 0.0907, T = 178 K.